PENGGESERAN TANGGUNG JAWAB TINDAK HUKUM ADMINISTRASI KE TINDAK PIDANA KORUPSI DALAM KASUS DISKRESI HUKUM PEJABAT TATA USAHA - Marcus Lukman (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
Administrative Legal Action by Administrative Official which is on based in discretionary power can not always be shifted to become the criminal law responsibility. Because each the law area owning justification value in with the concept and its legal norm. Although, an action of